Isolation of novel Steroidal Saponin from the stem extract of Andrographis echioides L.Nees - Diana, I Helen; Sundarapandiyan, Vanathi (International Journal of Environment, Agriculture and Biotechnology, 2024)
The field of ethnopharmacology recommends the use of traditional approaches for the development of drugs from natural sources. The herbaceous species Andrographis echioides, commonly found in the dry regions of the Indian subcontinent and Sri Lanka, was the subject of the present study, which aimed to test this hypothesis by isolating and characterizing compounds from the plant. Specimens were collected from Trichy and identified using monographic data. The ethanolic extract was subjected to preliminary analysis, and chromatographic techniques were employed to separate secondary metabolites. The bioactive compounds were then characterized to determine their chemical compositions and molecular structures. This study emphasizes the significance of natural medicines, specifically focusing on diosgenin, a secondary metabolite found in Andrographis echioides. HPTLC analysis of the ethanolic extract revealed promising results, with Rf values similar to those obtained by ultraviolet spectrum analysis. IR analysis indicated the presence of chemical groups with distinct peak formation, while NMR results demonstrated the intricate structure of the molecules and their associated chemical groups. In conclusion, harnessing the power of natural sources in the pharmaceutical industry has the potential to revolutionize drug discovery and development, as long as the challenges associated with standardization, quality control, and safety are addressed.